Clinical impact of uncommon epidermal growth factor receptor exon 19 insertion-deletion variants on epidermal growth factor receptor-tyrosine kinase inhibitor efficacy in non-small-cell lung cancer. (December 2020) - Peng, Xingzhou; Long, Xiaoyan; Liu, Li; Zeng, Liang; Yang, Haiyan; Jiang, Wenjuan; Liao, Dehua; Li, Kunyan; Wang, Jing; Lizaso, Analyn; Mao, Xinru; Xu, Qinqin; et al.
Abstract: Aim: Our study aimed to evaluate the efficacy and resistance mechanisms of first-line epidermal growth factor receptor (EGFR) inhibitor therapy in patients with advanced non–small-cell lung cancer (NSCLC) harbouring uncommon EGFR exon 19 deletion-insertion (19delins) variants. Methods: Targeted sequencing data of 2467 treatment-naive patients with NSCLC from January 2015 to August 2018 were retrospectively screened for EGFR exon 19 deletion (19del) variants. Clinical outcomes of 93 patients with uncommon EGFR 19delins and 93 patients with common EGFR 19del were selected through propensity score matching at a ratio of 1:1. Results: We identified 10 previously unreported EGFR 19delins variants. L747_P753delinsS, L747_A750delinsP and E746_S752delinsV were the most frequent variants, accounting for 33.1% (42/127), 23.6% (30/127) and 12.6% (16/127) of the cases, respectively. Despite similar baseline characteristics, treatment history and response rates, patients with uncommon 19delins had significantly longer median progression-free survival (mPFS) than those with common 19del (19.0 months vs. 13.0 months; p = 0.0016). At progression from first-line EGFR inhibitor therapy, patients with uncommon 19delins and common 19del had similar rates of developing resistance mechanisms including the acquisition of EGFR T790M (45.8% vs 57.8%), small-cell transformation (3.4% vs 3.6%) and MET amplification (5.1% vs 4.8%). For patients whose tumours acquired T790M and who received second-line osimertinib, the mPFS was significantly shorter for patients with uncommon 19delins (n = 27) than those with common 19del (n = 47, 5.0 months vs. 12.0 months; p < 0.0001). Conclusion: Our results suggest that patients with uncommon EGFR 19delins have improved clinical outcomes with first-generation EGFR inhibitor treatment, but inferior outcomes upon the development of T790M resistance mutations. Highlights: Patients with uncommon epidermal growth factor receptor ( EGFR ) exon 19 deletion-insertion (19delins) and common EGFR exon 19 deletion had distinct survival outcomes. Patients with uncommon EGFR 19delins had longer progression-free survival (PFS) with front-line EGFR tyrosine kinase inhibitor therapy. Patients with 19delins who acquired EGFR T790M had shorter PFS with osimertinib treatment. Patients with uncommon 19delins had superior response to first-line osimertinib therapy.